Standardisation in TVET teacher education - Dittrich, Joachim [Mitarbeiter]; Yunos, Jailani Md [Mitarbeiter]; Spöttl, Georg [Mitarbeiter]; Bukit, Masriam [Mitarbeiter]; Davies, Brenig [Mitarbeiter]; Papier, Joy [Mitarbeiter]; Knight, James A. [Mitarbeiter]; Elliot, Jack F. [Mitarbeiter]; Lucas, Norman [Mitarbeiter]; Nasta, Tony [Mitarbeiter]; Quiding, Yu [Mitarbeiter]; Yan, Yu [Mitarbeiter]; et al. (Lang, 2009)
Diese Publikation basiert auf den Ergebnissen des "First World Congress on Teacher Education for Technical and Vocational Education and Training - Shaping TVET Teacher Education for the Changing World of Work", der vom 21. bis 23. Juli 2008 in Bandung, Indonesien, stattfand. Der Kongress hatte zwei thematische Schwerpunkte: Einerseits wird aus einer internationalen Perspektive untersucht, welche Anforderungen an die Ausbildung von Lehrern in der technischen und beruflichen Bildung in einer sich ständig wandelnden Arbeitswelt zu stellen sind. Der zweite Fokus liegt auf der Analyse bereits existierender Ansätze der Standardisierung der Lehrerausbildung. Zum Abschluss ist die Erklärung der Konferenz ('Banburg Declaration on TVET Teacher Education') abgedruckt. Sie ruft dazu auf, angemessene Maßnahmen zur Verbesserung der Lehrerbildung in Angriff zu nehmen. (BIBB-Doku)

"Standardisation in TVET Teacher Education discusses issues connected with quality development in teacher education for Technical and Vocational Education and Training (TVET). Starting from some insight in the requirements on teacher education for TVET from different regions of the world, reflections on existing standardisation approaches for TVET Teacher Education from different perspectives are presented. A number of initiatives that are already implemented in order to solve specific issues in TVET Teacher Education are described. Finally, some of the approaches and concepts that were developed in the course of the EU Asia Link cofunded project 'Development of Transnational Standards for Teacher Training for Technical and Vocational Education and Training (TT-TVET) with a Multidisciplinary and Industrial Orientation' are presented. The majority of contributions were presented and discussed during the 'First World Congress on Teacher Education for Technical and Vocational Education and Training - Shaping TVET Teacher Education for the Changing World of Work' held in Bandung, Indonesia, in July 2008 which led to the Bandung Declaration on TVET Teacher Education." (Verlag)
Keywords: P 3.2.3 Lehrer; I 2.2 Europa; I 2.3.4 Asien; Berufsschullehrer; Lehrerbildung; Europäische Union; Asien